Controllable atomic layer deposition of one-dimensional nanotubular TiO2 - Meng, Xiangbo; Banis, Mohammad Norouzi; Geng, Dongsheng; Li, Xifei; Zhang, Yong; Li, Ruying; Abou-Rachid, Hakima; Sun, Xueliang (Applied surface science, 2013)
► One-dimensional TiO2 nanotubes were synthesized by atomic layer deposition (ALD). ► Two substrates were used in ALD-TiO2, anodic aluminum oxide (AAO) and carbon nanotubes (CNTs). ► The two routes resulted in pure TiO2 nanotube arrays and coaxial TiO2-CNT nanotubes, respectively. ► The TiO2 nanotubes could be tuned from amorphous to crystalline phase in the range 150–250°C. ► The TiO2 nanotubes could also be controlled on their wall thickness. This study aimed at synthesizing one-dimensional (1D) nanostructures of TiO2 using atomic layer deposition (ALD) on anodic aluminum oxide (AAO) templates and carbon nanotubes (CNTs). The precursors used are titanium tetraisopropoxide (TTIP, Ti(OCH(CH3)2)4) and deionized water. It was found that the morphologies and structural phases of as-deposited TiO2 are controllable through adjusting cycling numbers of ALD and growth temperatures. Commonly, a low temperature (150°C) produced amorphous TiO2 while a high temperature (250°C) led to crystalline anatase TiO2 on both AAO and CNTs. In addition, it was revealed that the deposition of TiO2 is also subject to the influences of the applied substrates. The work well demonstrated that ALD is a precise route to synthesize 1D nanostructures of TiO2. The resultant nanostructured TiO2 can be important candidates in many applications, such as water splitting, solar cells, lithium-ion batteries, and gas sensors.